RETRACTED: Elimination of damage to parts and disruption of mating seats - Shcherbakova Irina; Kovalchuk Nadezhda (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001